F#3.0 - Strongly-Typed Language Support for Internet-Scale Information Sources - Syme, Don; Battocchi, Keith; Takeda, Kenji; Malayeri, Donna; Fisher, Jomo; Hu, Jack; Liu, Tao; McNamara, Brian; Quirk, Daniel; Taveggia, Matteo; Chae, Wonseok; Matsveyeu, Uladzimir; et al. (Microsoft Research, 2012)
A growing trend in both the theory and practice of programming is the interaction between programming and rich information spaces. From databases to web services to the semantic web to cloud-based data, the need to integrate programming with heterogeneous, connected, richly structured, streaming and evolving information sources is ever-increasing. Most modern applications incorporate one or more external information sources as integral components. Providing strongly typed access to these sources is a key consideration for strongly-typed programming languages, to insure low impedance mismatch in information access. At this scale, information integration strategies based on library design and code generation are manual, clumsy, and do not handle the internet-scale information sources now encountered in enterprise, web and cloud environments. In this report we describe the design and implementation of the type provider mechanism in F# 3.0 and its applications to typed programming with web ontologies, web-services, systems management information, database mappings, data markets, content management systems, economic data and hosted scripting. Type soundness becomes relative to the soundness of the type providers and the schema change in information sources, but the role of types in information-rich programming tasks is massively expanded, especially through tooling that benefits from rich types in explorative programming.